Progression of Acute Kidney Injury to Chronic Kidney Disease in Sepsis Survivors: 1-Year Follow-Up Study. (October 2021) - Arshad, Ainan; Ayaz, Ahmed; Rehman, Sarah; Ukrani, Ronika Devi; Akbar, Inaara; Jamil, Bushra
Background: Despite the fact that septic acute kidney injury (AKI) is considered to be reversible, it can result in permanent kidney damage. Unfortunately, there is a scarcity of long-term follow-up studies highlighting progression to chronic kidney disease (CKD) in sepsis survivors. To address this issue, we conducted this study to assess the development of CKD in sepsis patients with AKI, and to identify risk factors associated with its development. Methods: This retrospective cohort study evaluated medical records of patients admitted at the Aga Khan University Hospital between January-December 2017 with the diagnosis of sepsis and subsequent development of acute kidney injury (AKI). One-year follow-up data was then analyzed to determine whether the AKI resolved or progressed to chronic kidney disease. Results: 1636 sepsis patients were admitted during the study period, out of which 996 (61%) met the inclusion criteria. 612 (61%) developed AKI during the admission. Mortality rate in the AKI group was 44% (n = 272). After 1 year, 47 (19%) patients eventually went on to develop CKD and 81% (n = 195) recovered fully. Risk factors for development of CKD were age ≥ 60 years (p = <0.001), diabetes (p = <0.001), hypertension (p = 0.001) and history of ischemic heart disease (p = <0.001). Conclusion: Mortality rates in sepsis are alarmingly high and even those patients who manage to survive are at risk of developing permanent organ dysfunction. Our study revealed that almost one fifth of all septic AKI survivors went on to develop chronic kidney disease within 1 year, even when AKI was not severe. We recommend that clinicians focus on early recovery of renal function, irrespective of AKI severity, and ensure robust follow-up monitoring to reduce long term morbidity and mortality associated with this devastating illness.